Sewage sludge treatment via hydrothermal carbonization combined with supercritical water gasification: Fuel production and pollution degradation. (July 2023) - Feng, Hongyu; Cui, Jintao; Xu, Zhang; Hantoko, Dwi; Zhong, Li; Xu, Donghai; Yan, Mi
Abstract: Aqueous phase byproduct from hydrothermal carbonization of sludge (named AHT) has high COD and TOC, supercritical water gasification (SCWG)can efficiently convert AHT into rich-H2 syngas. This study investigated the effect of temperature on syngas production, elements distribution and pollutants decomposition during the HTC of sewage sludge and SCWG of AHT. Compared to traditional directly SCWG of sludge, the combined method could produce syngas with higher H2 proportion and lower gaseous sulfur concentration. The maximum H2 proportion and carbon conversion efficiency (CE) in syngas could reach 59% and 30.40%. Meanwhile, higher SCWG temperature can reduce the sulfur concentration of syngas. SCWG effectively reduce the COD and TOC in AHT. With HTC and SCWG temperature increased, the concentration of total nitrogen (TN) gradually decreased but NH4 + ions concentration (NH4 + -N) increased in aqueous phase product. Graphical abstract: Image 1